COGNITIVE APPROACHES TO “INDIAN KILLER” BY SHERMAN ALEXIE (SCIENCE TIME JOURNAL, 2026)
This article analyzes Sherman Alexie’s Indian Killer from the perspective of cognitive poetics. The relevance of the study lies in the continuing importance of racial identity, cultural trauma, and stereotype formation in contemporary literary discourse. The research addresses the problem of how meaning is constructed in the novel and how identity crisis is cognitively framed in readers’ perception. To solve this problem, the study applies key cognitive theories, including figure–ground organization, prototype theory, cognitive deixis, scripts and schemas, and conceptual metaphor. The methodological approach focuses on identifying linguistic and narrative patterns that guide readers’ mental processing and emotional engagement in the fiction. The findings demonstrate that the novel functions not only as a crime narrative but as a complex cognitive and discursive structure shaping readers’ understanding of cultural conflict and social tension. The study concludes that cognitive poetics provides an effective analytical base for interpreting identity formation and racial discourse in modern literature, contributing to both literary theory and interdisciplinary cognitive research.